P3.102 Infant outcomes of maternal syphilis cases diagnosed in british columbia, canada 2010–2016. (8th July 2017) - Wong, J; Arkell, C; Durigon, M; Makaroff, S; Montgomery, C; Morshed, M; Money, D; Schalkwyk, J van; King, A; Gilbert, M; Grennan, T; Ogilvie, G
Abstract : Introduction: In British Columbia (BC), Canada, 2 reported cases of congenital syphilis have been confirmed for the years 2010–2016. However, USA has reported increases in congenital syphilis cases. We sought to characterise outcomes of infants born to pregnant or recently pregnant mothers diagnosed with syphilis in BC to identify areas to strengthen syphilis prevention programming. Methods: All positive syphilis tests in BC are reviewed by centrally-located expert clinicians who diagnose, stage, and provide treatment recommendations. Infant outcome information for all syphilis cases (primary, secondary, early and late latent) diagnosed in pregnant women (or within 90 days after delivery) from January 2010 to July 2016 were collected and analysed descriptively. Results: 45 maternal syphilis cases (18 early latent, 27 late latent) were reported from Jan 2010 to July 2016. Of the 45 cases, 36 had a live birth, 5 had a 1 st trimester miscarriage, 1 had a therapeutic abortion, 1 lost her fetus due to a motor vehicle collision, and 2 had not delivered her baby yet as of Sept 2016. Of the 36 mothers with live births, 28 were treated within 4 weeks, 3 were treated after 4 weeks but greater than 30 days before delivery, 2 were treated less than 30 days before delivery, and 3 were treated post-partum. For these 5 infants, 3 had mothers born outside Canada and 1 was in a marginalised population. All 5 infants were treated empirically with penicillin at delivery. 3 were RPR negative at birth, and 2 had titres lower than their mothers; by 3 months of age, both had a negative RPR. Conclusion: Most maternal syphilis cases are treated quickly after diagnosis. However, a few are treated shortly before delivery or after delivery. Strengthening early syphilis screening among mothers born outside Canada may be an area to focus on to help ensure adequate time for treatment before delivery. Communication with providers of the risk of congenital syphilis may also support prenatal syphilis screening and better capture of all congenital syphilis cases.